IDENTIFIKASI MORFOLOGI BERDASARKAN PENGUKURAN FETOMETRIK FETUS SAPI BALI DARI RUMAH POTONG HEWAN KOTA AMBON - Astriq Angriani Satha Kusuma; Demianus Ferdinand Souhoka; Jusak Labetubun (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aimed to identify the morphological characteristics and fetometric parameters of Bali cattle fetuses obtained from the Municipal Abattoir (RPH) of Ambon, and to examine the relationship between Crown–Rump Length (CRL) and gestational age. Thirty fetus samples were collected and measured using a measuring tape and a digital scale. Observed fetometric parameters included CRL, head length, head width, head circumference, and fetal body weight. Data were analyzed descriptively to determine the relationship between fetometric size and gestational age. Results showed that fetal morphology developed consistently with increasing CRL. At CRL 21–31 cm (±90–120 days), skin pigmentation and tactile hair appeared; CRL 32–44 cm (±120–150 days) indicated external genital development; CRL 45–56 cm (±150–180 days) showed hair growth on the tail and ears; and CRL 57–70 cm (±180–210 days) exhibited morphology similar to newborn calves. The relationship between CRL and gestational age followed a non-linear pattern consistent with physiological fetal growth. It was concluded that CRL and fetal weight serve as reliable indicators for estimating gestational age in Bali cattle. The fetometry-based prediction model developed in this study could be applied as a practical tool in field or abattoir conditions, although further validation with larger and more diverse samples is recommended.